WATER IN THE VISUAL STRUCTURE OF DIGITAL COMIC BANG GABER BY RIZAL FAHMI - Syarip Hidayat; Ranti Rachmawanti (Proceeding Bali-Bhuwana Waskita: Global Art Creativity Conference, 2022)
Water is a natural element for human survival, not just fulfilling daily needs in activities such as drinking, bathing, and others. Water has a crucial role in the process of life. This role indicates that water is a symbol attached to every living thing, especially humans. The relationship between water and humans is often visualized in various forms and mediums. One of them is in the digital comic Bang Gaber by Rizal Fahmi, which features the element of water in the digital comic theme. The use of water elements and symbols is one of the attractions of the digital comic to be studied more deeply related to its visual structure. This research is included in the Qualitative, using an approach to the Science of Fine Arts (Comic). The data source is Rizal Fahmi, comic artist of Bang Gaber, taken from Instagram. Data collection techniques through observation and visual studies. Data analysis with the support of the relevant literature review on the visual structure. The theory used to analyze is the structuralism theory of Levi-Strauss about the structure in a comic artwork. The research results show that the visual structure of digital comics with the theme of water in comics consists of the surface structure as a tangible visualization of water as an object that delivers philosophical thinking in life and is symbolized metaphorically. At the same time, deep structures are in the form of wisdom, toughness, and self-acceptance. Given that Bang Gaber's Digital Comics is one of the revivals of Indonesian comics, comic book fans may easily access them. Visual analysis is necessary to uncover the emerging visual structure and understand this digital comic's messages and meanings.